The economic impact of machine perfusion technology in liver transplantation - Boteon, Yuri L.; Hessheimer, Amelia J.; Brüggenwirth, Isabel M. A.; Boteon, Amanda P. C. S.; Padilla, María; Meijer, Vincent E.; Domínguez‐Gil, Beatriz; Porte, Robert J.; Perera, M. Thamara P. R.; Martins, Paulo N. (Artificial organs, 2022)
Introduction Several clinical studies have demonstrated the safety, feasibility, and efficacy of machine perfusion in liver transplantation, although its economic outcomes are still underexplored. This review aimed to examine the costs related to machine perfusion and its associated outcomes. Methods Expert opinion of several groups representing different machine perfusion modalities. Critical analysis of the published literature reporting the economic outcomes of the most used techniques of machine perfusion in liver transplantation (normothermic and hypothermic ex situ machine perfusion and in situ normothermic regional perfusion). Results Machine perfusion costs include disposable components of the perfusion device, perfusate components, personnel and facility fees, and depreciation of the perfusion device or device lease fee. The limited current literature suggests that although this upfront cost varies between perfusion modalities, its use is highly likely to be cost‐effective. Optimization of the donor liver utilization rate, local conditions of transplant programs (long waiting list times and higher MELD scores), a decreased rate of complications, changes in logistics, and length of hospital stay are potential cost savings points that must highlight the expected benefits of this intervention. An additional unaccounted factor is that machine perfusion optimizing donor organ utilization allows patients to be transplanted earlier, avoiding clinical deterioration while on the waiting list and the costs associated with hospital admissions and other required procedures. Conclusion So far, the clinical benefits have guided machine perfusion implementation in liver transplantation. Albeit there is data suggesting the economic benefit of the technique, further investigation of its costs to healthcare systems and society and associated outcomes is needed. Up to now, the clinical benefits have guided machine perfusion implementation in liver transplantation. In this expert opinion of several groups representing different machine perfusion modalities, a critical analysis of the published literature reporting the economic outcomes of the most used techniques of machine perfusion in liver transplantation was performed. The limited current literature suggests that although this upfront cost varies between perfusion modalities, its use is highly likely to be cost‐effective.